Örgüt Tasarımında Yeni Tekniklerin Yayılım Dinamikleri - (:unkn) unknown (My University, 2003)
0

This study focuses on the institutional and rational determinants of organizational practices. Environmental pressures, forces for conformity and organizational characteristics determine in large measure the speed and strength with which organizational practice are adopted in a given organization. Institutional determinants have a strong effect on the application of new practices. Organizations seek support and legitimacy in their institutional fields by adopting structural models that are generally perceived to be the best available.